Integrated massively parallel sequencing of 15 autosomal STRs and Amelogenin using a simplified library preparation approach. Issue 12 (25th April 2018) - Xue, Jian; Wu, Riga; Pan, Yajiao; Wang, Shunxia; Qu, Baowang; Qin, Ying; Shi, Yuequn; Zhang, Chuchu; Li, Ran; Zhang, Liyan; Zhou, Cheng; Sun, Hongyu
Abstract: Massively parallel sequencing (MPS) technologies, also termed as next‐generation sequencing (NGS), are becoming increasingly popular in study of short tandem repeats (STR). However, current library preparation methods are usually based on ligation or two‐round PCR that requires more steps, making it time‐consuming (about 2 days), laborious and expensive. In this study, a 16‐plex STR typing system was designed with fusion primer strategy based on the Ion Torrent S5 XL platform which could effectively resolve the above challenges for forensic DNA database‐type samples (bloodstains, saliva stains, etc.). The efficiency of this system was tested in 253 Han Chinese participants. The libraries were prepared without DNA isolation and adapter ligation, and the whole process only required approximately 5 h. The proportion of thoroughly genotyped samples in which all the 16 loci were successfully genotyped was 86% (220/256). Of the samples, 99.7% showed 100% concordance between NGS‐based STR typing and capillary electrophoresis (CE)‐based STR typing. The inconsistency might have been caused by off‐ladder alleles and mutations in primer binding sites. Overall, this panel enabled the large‐scale genotyping of the DNA samples with controlled quality and quantity because it is a simple, operation‐friendly process flow that saves labor,  time and costs.